New onset episodic vertigo as a presentation of vestibular neuritis - Tang, Lu; Jiang, Weiwei; Wang, Xiaoshan (Frontiers in Neurology, 2022)
Objective Vestibular neuritis (VN) is a common peripheral cause of acute vestibular syndrome, characterized by sustained vertigo and gait instability, persisting from 1 day to several weeks. With the widespread use of comprehensive vestibular function tests, patients with VN and non-sustained vertigo have drawn attention. In this study, we retrospectively analyzed the clinical presentation of patients with VN and episodic vertigo, aiming to expand the atypical clinical features of VN. Methods This retrospective study enrolled 58 patients with VN. Among them, 11 patients with more than 3 remissions per day, each lasting over 1 h were assigned to the episodic vertigo (EV) group, and 47 subjects without significant relief into the sustained vertigo (SV) group. Demographic information, clinical manifestations and data of supplementary examinations were collected and statistically analyzed. These patients were followed up 1 year after discharge to gather prognostic information. Results The incidence of spontaneous nystagmus (SN) and proportion of severe vertigo (Dizziness Handicap Inventory questionnaire score >60) in the SV group were significantly higher than those in the EV group. Spearman correlation showed that with a longer disease course, the velocity of overt saccade was smaller (p < 0.05, Rs = −0.263) in all patients with VN. Conclusion The non-sustained manifestations in VN overlap with a wider spectrum of other vestibular disorders and stroke-related vertigo, which add an additional layer of complexity to the differential diagnosis of new onset episodic vertigo. By retrospectively analyzing the clinical characteristics and vHIT parameters, our study has expounded on the atypical features and potential pathophysiological mechanism of episodic syndromes in VN. VOR gain and saccades measured by vHIT could be reliable indicators for vestibular rehabilitation process.